2015
DOI: 10.1016/j.toxrep.2015.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic and nicotine co-exposure lead to some synergistic effects on oxidative stress and apoptotic markers in young rat blood, liver, kidneys and brain

Abstract: Arsenic and nicotine exposure has been a major health concern globally. Individually both these toxicants increase the risk to various diseases including cancers. However, limited information exists on the co-exposure. In this study, we evaluate the effects of their individual and combined exposure and if co-exposure to these toxicants might have a synergism or antagonism. Male rats were exposed to a very low dose of arsenic (25 ppm in drinking water) or nicotine (0.25 mg/kg, sub-cutaneously) for a period of 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 68 publications
5
7
1
Order By: Relevance
“…In the current study, Ar administration significantly reduced enzymatic antioxidants such as SOD, CAT, GPx, GST, and GR in comparison to controls. This result was well in line with an earlier report by Jain et al ( 2015 ), who observed lower levels of enzymatic antioxidants in arsenic-treated rat kidneys. Similarly, Gong et al ( 2015 ) observed a reduction in enzymatic antioxidants in Ar-treated rats, mainly due to oxidative stress and unpaired electrons in the renal tissue.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the current study, Ar administration significantly reduced enzymatic antioxidants such as SOD, CAT, GPx, GST, and GR in comparison to controls. This result was well in line with an earlier report by Jain et al ( 2015 ), who observed lower levels of enzymatic antioxidants in arsenic-treated rat kidneys. Similarly, Gong et al ( 2015 ) observed a reduction in enzymatic antioxidants in Ar-treated rats, mainly due to oxidative stress and unpaired electrons in the renal tissue.…”
Section: Discussionsupporting
confidence: 93%
“…One organ typically affected by Ar-induced ROS production is the kidney (Prabu and Muthumani 2012 ). In the current study, a notable increase in ROS was found in the blood and renal tissue of Ar-intoxicated rats versus controls, which confirms earlier reports (Jain et al 2015 ). This may be due to the induction by Ar of a complex chain of one-electron reduction of molecular oxygen, which first leads to the formation of superoxide radicals (O 2 ) in the kidney.…”
Section: Discussionsupporting
confidence: 93%
“…Simultaneous exposure of both the toxicants produced more pronounced increase in oxidation of membrane lipids (401.2%) and proteins (40.0%) of renal tissue compared to control as well as exposure of either toxicant ( Table 1 ). These observations are in accordance with the observations reported with co-exposure of metals and insecticides to rats [ 39 , 41 , 46 ].…”
Section: Resultssupporting
confidence: 93%
“…Co-exposure to IMI and arsenic produced more pronounced fall in TTH level (63.8%) in renal tissue as compared to control ( Table 1 ). Similar decline in TTH level have also been reported in different visceral organs in arsenic exposed rats [ [46] , [47] , [48] ].…”
Section: Resultssupporting
confidence: 84%
“…However some in-vitro and in-vivo studies suggested that carcinogenic potency of DMA is more than that of sodium arsenite. 52,53 Our results although in some disagreement with available literature and observed arsenic (III) to be more carcinogenic than DMA possibly due to deteriorative effects of DMA via oral route.…”
Section: Discussioncontrasting
confidence: 81%